1995
DOI: 10.2307/30140946
|View full text |Cite
|
Sign up to set email alerts
|

Association of Legionnaires' Disease with Construction: Contamination of Potable Water?

Abstract: There was widespread contamination of potable water with Legionella pneumophila during a period of major construction; cooling towers were without growth of Legionella. One patient's isolate was the same by PFGE as the environmental isolate collected from the water faucet in his room. Control measures included superheating water used in all patient care areas to 75 degrees C for 72 hours and flushing superheated water through faucets and showers; cleaning shower heads with a sonicator washer; and raising the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 28 publications
0
13
0
4
Order By: Relevance
“…Inhalation of aerosols or microaspiration of contaminated water has been recognized as a source of legionellosis (227). After the initial description of an outbreak of severe respiratory disease occurring in Pennsylvania, which showed that person-to-person transmission was unlikely (77), subsequent reports of Legionella infections were repeatedly associated with contaminated water in both communityacquired (165,229) and nosocomial (30,90,140,142,176) settings. The ecology of L. pneumophila was extensively studied and confirmed empirical observations of its predilection for growth in hot water tanks and its localization in sediment (228).…”
Section: Legionellaceaementioning
confidence: 99%
“…Inhalation of aerosols or microaspiration of contaminated water has been recognized as a source of legionellosis (227). After the initial description of an outbreak of severe respiratory disease occurring in Pennsylvania, which showed that person-to-person transmission was unlikely (77), subsequent reports of Legionella infections were repeatedly associated with contaminated water in both communityacquired (165,229) and nosocomial (30,90,140,142,176) settings. The ecology of L. pneumophila was extensively studied and confirmed empirical observations of its predilection for growth in hot water tanks and its localization in sediment (228).…”
Section: Legionellaceaementioning
confidence: 99%
“…Some outbreaks of legionellosis have been associated with construction, and it was originally believed that the bacteria could survive and be transmitted to humans via soil. However, L. pneumophila does not survive in dry environments, and these outbreaks are more likely the result of massive descalement of plumbing systems due to changes in water pressure during construction (159,205).…”
Section: Microbial Ecologymentioning
confidence: 99%
“…Aspergillus and Legionella species are the leading causes of construction-related HAIs (213,240,281). Legionella species are ubiquitous aquatic organisms commonly isolated from water (281).…”
Section: Facility Construction and Renovationmentioning
confidence: 99%